The Effect of Service Quality on Consumer Satisfaction: A Case Study of the Hospitality Industry in Pekanbaru Indonesia - Harwina, Yulia (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
The purpose of this study was to determine the effect of service quality on customer satisfaction at Hotel Pekanbaru ''. The research method used is quantitative research. The sampling technique used incidental random sampling, with samples taken using the Slovin formula as many as 97 people. Finding Based on the partial test (test) it was found that there was a significant influence between service quality and Pekanbaru Hotel consumer satisfaction. It was also found that service quality contributed 95.3% to customer satisfaction while 4.7% was determined by other variables not included in this research.